CIPP Evaluation of Counseling Guidance Programs - Sundaya, Jemi; Montanesa, Dian (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Moral problems become student problems that occur as part of the impact of globalization. This research aimed to evaluate guidance and counseling services at MAN 1 Bengkulu Utara as supporting students in solving their problems and developing their potential. The evaluation model used is the CIPP (Context, Input, Process, Product) evaluation model to get a more comprehensive and in-depth picture of the guidance and counseling program. This research used a descriptive method with a qualitative approach. Data was obtained from guidance and counseling coordinators, guidance and counseling teachers and students using interview techniques, document study, and observation. The results of the research showed that in the Context aspect, achievement is in the high category, as well as in the program Input aspect which is also in the high category. Meanwhile, the Process program aspect is also in the high category, but the Product aspect is in the medium category. The conclusion is that the guidance and counseling program can be said to be well implemented. Only moderate product categories still need to be improved. Furthermore, to improve program implementation, there are several recommendations, including the preparation of special documents for guidance and counseling profiles; documents detailing special funds for guidance and counseling programs; and additional guidance and counseling teachers.